Projeto e avaliação de desempenho de uma prótese virtual transtibial externa para pessoas com deficiência - Barros, Thiago Koga (Universidade Federal de São Carlos, 2023)
Devices known as prostheses and orthotics are commonly used to aid mobility and improve the quality of life of people with disabilities, supplying and meeting biomechanical needs for the absence of limbs or treatment and functionality of the musculoskeletal system. However, in Brazil there are not many properly documented projects on how to perform the necessary tests and performance validations of these same devices for the necessary reliability for development. Thus, the objective of this work is to design a virtual transtibial prosthesis, detailing the processes and validating the performance by CAD/CAE based on international parameterizations in accordance with the current standards on the subject. Initially, a modeling of all the necessary components was made in CAD. Subsequently, a simulation of the complete structure and parameters for declared configurations was carried out, which resulted in a proposal for a prototype with proof test validations of the static type with loading conditions for patients of up to 100 kg. Acceptable values of forces, deformations and safety coefficients were obtained for the structure, validating the process and applied methodology.
Design and performance evaluation of an external transtibial virtual prosthesis for people with disabilities
Keywords: Prótese; Transtibial; CAD/CAE; Simulações de comprovação; Prosthetics; Proof simulations; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA::TECNOLOGIA DE PROTESES